The Impact of Students’Realization of Stress Placement on Identifying the Class of the English Word and Its Meaning - Muslih Shwaysh Ahmed (International Journal of Psychosocial Rehabilitation, 2025)
The present study is an attempt to show the effect of the university students’ realization of stress placement on the identification of the class of the English word and its meaning. The study postulates that most Iraqi University students who study English as a foreign language know that the syllable should be stressed to give the intended class or meaning of words. To achieve the aim of the study, a written test which consists of twenty words and phrases distributed over three questions was prepared by the researcher.Before the final administration of this test, its validity and reliability have been proved. The participants involved in the study who were chosen randomly are asked to transcribe the words and phrases phonemically and put the primary stress [ ’ ] on the proper syllable as required in the test. The participants are 48 and they represent 37% of the population of the study.All of them studied phonetics and phonology at the Department of English, College of Education for Humanities , University of Anbar and their native language is Arabic.The analysis of the test reveals that the correct answers of the students in the three questions of the test are less than the wrong ones.The percentages of the correct answers of these questions are 44% , 31% and 26% , respectively, whereas the percentages of the wrong answers are 54%, 67% and 62%, respectively. These findings invalidate the hypothesis of the research. In the light of the findings of the study , the researcher comes up with a number of conclusions among them, stress is a problematic area that faces Iraqi university students due to certain factors such as the great influence of the firmly established linguistic habits of the learner’s native language on the process of learning a foreign language.